THE INFLUENCE OF QUALITY PRODUCTS AND QUALITY OF CUSTOMER LOYALTY IN CIGARETTE CLASS MILD(CASE STUDIES IN PT.NIAGA NUSAABADI BANDAR LAMPUNG) - Farida Efriyanti; Ferdy Rahman (UBL, 2016)
This research is motivated a condition that is now increasingly fast-moving business where competition is more advanced in the field of cigarettes. Integration thus a need to have a marketing strategy in order to maintain and towards higher market share. As for the issue of this study is